Quantitative estimation of disposition index from postprandial glucose data across the spectrum of glucose tolerance - Schiavon, Michele; Vella, Adrian; Dalla Man, Chiara (American journal of physiology: endocrinology and metabolism, 2025)
The advent of continuous glucose monitoring (CGM) in non-insulin-treated individuals raises the possibility of quantifying disposition index (DI), a key metric of β-cell function usually assessed in research settings, in outpatients. A method for DI estimation from postprandial glucose data only (DI G ) was developed and validated against a reference. DI G can be used to assess therapy effectiveness and degree of glucose tolerance in non-insulin-treated individuals, paving the way for its quantification in real-life conditions from CGM devices. Disposition index (DI), defined as the product of insulin sensitivity and β-cell responsivity, is the best measure of β-cell function. This is usually assessed from plasma glucose and insulin, and sometimes C-peptide, data either from surrogate indices or model-based methods. However, the recent advent of continuous glucose monitoring (CGM) systems in non-insulin-treated individuals raises the possibility of its quantification in outpatients. As a first step, we propose a method to assess DI from glucose concentration data only and validated it against the oral minimal model (OMM). To do so, we used data from two clinical dataset with mixed meal tolerance test (MTT) studies in non-insulin-treated individuals: the first consisted of 14 individuals with type 2 diabetes studied twice, either after receiving a DPP-4 inhibitor or a placebo before the meal, whereas the second consisted of 62 individuals with and without pre- or type 2 diabetes. A third, simulated, dataset consisted of 100 virtual subjects from the Padova Type 2 Diabetes Simulator was used for additional tests. Plasma glucose, insulin, and C-peptide concentrations were used to estimate the reference DI from the OMM (DI MM ), whereas glucose data only were used to calculate the proposed DI (DI G ). DI G was well correlated with DI MM in both the clinical and simulated datasets ( R between 0.88 and 0.79, P < 0.001), and exhibited the same between-visit or between-group pattern. DI G can be used to assess therapy effectiveness and degree of glucose tolerance using glucose data only, paving the way to potentially assess β-cell function in real-life conditions using CGM. NEW & NOTEWORTHY The advent of continuous glucose monitoring (CGM) in non-insulin-treated individuals raises the possibility of quantifying disposition index (DI), a key metric of β-cell function usually assessed in research settings, in outpatients. A method for DI estimation from postprandial glucose data only (DI G ) was developed and validated against a reference. DI G can be used to assess therapy effectiveness and degree of glucose tolerance in non-insulin-treated individuals, paving the way for its quantification in real-life conditions from CGM devices.